2020
DOI: 10.1021/acs.langmuir.0c02871
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of Carrier-Mediated Delivery of siRNA in the Cell Membrane Using MD Simulation

Abstract: The effective translocation of small interfering RNA (siRNA) across cell membranes has become one of the main challenges in gene silencing therapy. In this study, we have carried out molecular dynamics simulations to investigate a systematic procedure with different carriers that could be convenient for efficient siRNA delivery into the cell. Starting with poly-amidoamine (PAMAM) dendrimers and cholesterol molecules as carriers, we have found cholesterol as the most efficient carrier for siRNA when it is coval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Most of the simulations of the automotive ACCS system are realized by using the pure software method through Matlab simulation, the hardware loop simulation platform (Hardware in the Loop, HIL) proposed by the author is in the environment of the embedded system, and simulates the environment of the real car; in this way, it is closer to the objective situation of the real car and improves the authenticity and reliability of the experimental environment [11]. Figure 1 is the hardware logic diagram of the automotive ACCS hardware loop simulation platform, the PC simulation terminal, and the embedded system exchange information through the necessary I/O interfaces, such as digital signals, analog signals, and serial ports.…”
Section: E Basic Idea Of Accs Designmentioning
confidence: 99%
“…Most of the simulations of the automotive ACCS system are realized by using the pure software method through Matlab simulation, the hardware loop simulation platform (Hardware in the Loop, HIL) proposed by the author is in the environment of the embedded system, and simulates the environment of the real car; in this way, it is closer to the objective situation of the real car and improves the authenticity and reliability of the experimental environment [11]. Figure 1 is the hardware logic diagram of the automotive ACCS hardware loop simulation platform, the PC simulation terminal, and the embedded system exchange information through the necessary I/O interfaces, such as digital signals, analog signals, and serial ports.…”
Section: E Basic Idea Of Accs Designmentioning
confidence: 99%
“…A wide range of carriers exist that help to cross siRNA through the cell membrane and protect it from degradation 66 . The siRNA-cholesterol conjugated is known as the best-conjugated system in siRNA delivery 45 . Despite this, the molecular details of the interaction of siRNA-cholesterol conjugated with the cell membrane and the effect of the ion condition on its efficacy are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the lipid conjugation systems could improve the efficiency of the siRNA delivery system 30 . In addition, between PAMAM (Poly amidoamine) and cholesterol as a carrier, cholesterol is a more efficient carrier for siRNA delivery than PAMAM 45 . The zwitterion lipids with low toxicity can be used as an alternative lipid delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…When the nucleus contracts, nuclear chromatin is highly concentrated at the edge of the nuclear membrane, and nucleoli are cleaved, accompanied by the formation of ladder-like DNA subunit fragments [14]. Then, the cell membrane invades and divides the apoptotic cell into several cells; the subunits wrapped in the bilayer membrane structure are called apoptotic bodies [15].…”
Section: Discussionmentioning
confidence: 99%